2019
DOI: 10.1080/13697137.2019.1622085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endogenous and exogenous progesterone exposure on stress biomarkers: a systematic review

Abstract: Stress activates the autonomic nervous system (ANS) and the hypothalamic-pituitary-adrenal axis (HPAA). Based on a systematic literature review of the impact of endogenous and exogenous exposure with natural progesterone on the stress response in healthy premenopausal and postmenopausal women, the following conclusions can be drawn: the HPAA activity was not relevantly affected by endogenous progesterone exposure across the menstrual cycle, but might be reduced by exogenous micronized progesterone application;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
(298 reference statements)
0
6
0
Order By: Relevance
“…To date, only seven studies (of roughly 49 currently available studies on cardiac vagal activity across the menstrual cycle as suggested by our meta-analysis [28] and a recent review [30]) have reported associations between ovarian hormone levels and cardiac vagal activity, with mixed results [27,[31][32][33][34][35][36]. However, four major methodological and statistical limitations in these studies prevent clear conclusions.…”
Section: Introductionmentioning
confidence: 77%
“…To date, only seven studies (of roughly 49 currently available studies on cardiac vagal activity across the menstrual cycle as suggested by our meta-analysis [28] and a recent review [30]) have reported associations between ovarian hormone levels and cardiac vagal activity, with mixed results [27,[31][32][33][34][35][36]. However, four major methodological and statistical limitations in these studies prevent clear conclusions.…”
Section: Introductionmentioning
confidence: 77%
“…The progestin-only contraceptives in this study used levonorgestrel, which differs from endogenous progesterone and may attenuate the magnitude of the phase-based increase in sympathetic activity caused by endogenous progesterone during the late luteal phase noticed with NM (30). Stadler et al (40) reviewed the effects of endogenous and exogenous progesterone on the ANS and hypothalamic–pituitary–adrenal axis, which are both activated by stressors. They noticed that the hypothalamic–pituitary–adrenal axis activity was not affected by endogenous progesterone exposure across the MC but might be reduced by exogenous progestin.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrus synchronisation and superovulation protocol may be a source of stress to the animal as administration of such hormones will alter the natural reproductive physiological process in the body of the animal (Stadler et al, 2019). Haematological indices such as erythrocyte count, packed cell volume, haemoglobin concentration and leucocyte counts are reliable markers of stress in animals (Vinodhini and Narayanan 2009).…”
Section: Discussionmentioning
confidence: 99%